Ideological Determinants of the Current Saudi-Iranian Rivalry in the Middle East - Osiewicz, Przemysław (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
The Saudi-Iranian rivalry reached a dramatic climax at the very beginning of January 2016. Unodoubtedly, Iran and Saudi Arabia represent two distinct political systems and two different approaches to foreign policy making. The question is, however, what are the reasons for these differences. It is a well-known fact that both Iranian and Saudi political systems are based on Islamic values. Yet the main difference is that their main principles stem from two divergent interpretations of Islam. The main aim of the article is to point up the main ideological differences between Iran and Saudi Arabia which directly or indirectly shape their foreign policies. Do they play a decisive role as far as the current tensions between Iran and Saudi Arabia are concerned? As far as sources are concerned, the analysis is based on official documents issued by Ministries of Foreign Affairs of Iran and Saudi Arabia as well as selected monographs and academic articles.

W styczniu 2016 roku miały miejsce niebezpieczne napięcia w stosunkach irańsko-saudyjskich. Bez wątpienia zarówno Iran, jak i Arabia Saudyjska reprezentują dwa odmienne systemy polityczne i dwa różne podejścia w kwestii formułowania celów polityki zagranicznej. Ważkie z badawczego punktu widzenia wydaje się wyjaśnienie przyczyn takiego stanu rzeczy, skoro podstawę obu systemów stanowią wartości islamu. Głównym celem niniejszego artykułu jest wskazanie najważniejszych ideologicznych różnic pomiędzy Iranem a Arabią Saudyjską, które mają bezpośredni lub tylko pośredni wpływ na prowadzoną przez nie politykę zagraniczną. Główne pytanie badawcze dotyczy z kolei ich możliwego wpływu na obecny stan stosunków na linii Iran–Arabia Saudyjska. Podstawę źródłową artykułu stanowią oficjalne dokumenty, opublikowane przez ministerstwa spraw zagranicznych obu państw, jak również wybrane monografie i artykuły naukowe.
Ideologiczne uwarunkowania irańsko-saudyjskiej rywalizacji w regionie Bliskiego Wschodu
Keywords: Iran; Saudi Arabia; the Syrian war; religious ideology; the Islamic State; Iran; Arabia Saudyjska; wojna w Syrii; ideologia religijna; Państwo Islamskie